When Brand, Quality, and Social Media Align: Insight into Wardah Face Cream Purchase Decisions - Afia Zahra Afzalurrizqi; Muhammad Abid Humam Abyan; Masitha Fahmi Wardhani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study investigates the influence of Brand Image, Product Quality, and the use of Social Media on consumers’ purchasing decisions to Wardah facial cream. Using a quantitative method with purposive sampling technique, this study involved 120 Wardah product users in the West Semarang area. Data were collected through an online questionnaire and processed using SmartPLS 4.0. The results indicate that product quality and social media usage have a positive and significant effect on purchasing decisions, whereas brand image shows a positive but insignificant effect. This suggests that consumers tend to prioritize tangible attributes such as product quality and active engagement through social media over brand perception The model explains 75.2% of the variance in purchasing decisions (Adjusted R² = 0.752), highlighting the strong explanatory power of the variables examined. Practically, the findings suggest that marketers should prioritize product quality and optimize social media campaigns to boost customer engagement and loyalty, while reassessing brand perception strategies.